Pengaruh Profesionalisme dan Etos Kerja terhadap Kinerja ASN melalui Komitmen pada Dinas Pendidikan Maluku Barat Daya - Siska Tenlima, Windy; N. C. Lewaherilla; A. Risambessy (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of professionalism and work ethic on the performance of Civil Servants (ASN), with commitment serving as a mediating variable at the Education and Culture Office of Southwest Maluku Regency. The study is motivated by the importance of improving ASN performance in public service institutions through strengthening professional attitudes, work ethic, and organizational commitment. The research employed a quantitative approach using the Partial Least Square (PLS) method with SmartPLS 3.0 software as the analytical tool. The sample consisted of 40 permanent ASN selected through purposive sampling techniques. The findings reveal that professionalism has a significant effect on commitment, although it does not directly influence ASN performance. Similarly, work ethic significantly affects commitment but does not directly affect ASN performance. Furthermore, commitment is proven to significantly mediate the relationship between professionalism and work ethic on ASN performance. These results indicate that improving professionalism and work ethic alone is insufficient to enhance ASN performance unless accompanied by strong organizational commitment. Therefore, commitment plays a strategic role in strengthening employee performance within government institutions and supporting the achievement of organizational goals effectively and sustainably.